1988
DOI: 10.1021/jm00399a004
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Trioxanes as potential antimalarial agents

Abstract: A number of 1,2,4-trioxanes were prepared and tested for antimalarial activity in search of a simplified analogue of the naturally occurring antimalarial qinghaosu. The compounds were assayed in an in vitro system for antimalarial activity against chloroquine-susceptible and chloroquine-resistant strains of Plasmodium falciparum. The most active compounds were methyl 2-(2,4a-epidioxy-4a,5,6,7,8,8a-hexahydro-5,5,8a-trimethyl-2H-1-benzop yra n-2-yl) acetate (3b), which showed IC20's of 96 and 39 ng/mL, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…1 Generally, singlet oxygen is the reagent of choice in these processes, requiring the use of an external sensitizer for the energy transfer process to occur. [2][3][4][5] During our studies on the photochemical behavior of dienones in the presence of molecular oxygen, we established an easy one-pot approach for the preparation of bridged 1,2,4-trioxanes (Scheme 1). [6][7][8] The process involves a singlet 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 oxygen Diels-Alder type oxygenation of 2H-pyran in situ generated intermediates, revealing the ability of dienones bearing an ionone-type skeleton to act as singlet oxygen sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, singlet oxygen is the reagent of choice in these processes, requiring the use of an external sensitizer for the energy transfer process to occur. [2][3][4][5] During our studies on the photochemical behavior of dienones in the presence of molecular oxygen, we established an easy one-pot approach for the preparation of bridged 1,2,4-trioxanes (Scheme 1). [6][7][8] The process involves a singlet 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 oxygen Diels-Alder type oxygenation of 2H-pyran in situ generated intermediates, revealing the ability of dienones bearing an ionone-type skeleton to act as singlet oxygen sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, 38b was inactive in the Rane test. 42,90 Trioxane 39 and its 3-hydroxymethyl and 3-hydroxyhexyl analogs were prepared by treating 1,4-dihydro-1,4-dimethyl-1,4-epidioxynaphthalene with the corresponding aldehydes in the presence of acid. The trioxolane alcohols were also converted into five carbamate and ester derivatives.…”
mentioning
confidence: 99%
“…Introduction. -Ever since the discovery that arteannuin (1) is a potent antimalarial agent [ 1-31, there has been a growing interest in the synthesis, chemistry, and physical properties of the intrinsic structural feature of this unique natural product, namely the 1,2,4-trioxane ring and its congeners [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. From a study of the vibrational spectra of 1 and its lactol derivatives, it has been concluded [18] that the peroxide linkage contained therein is characterized by a frequency at 722 cm-'.…”
mentioning
confidence: 99%